The speedy lingo game-mastering synonyms, antonyms and homonyms in a flash / Afni Anida Adnan … [et al.] - Adnan, Afni Anida; Nordin, Norsidah; Osman, Mohd Izwan; Abdul Halim, Muhammad Aiman (Research Innovation Business Unit, 2014)
Homonyms, synonyms and antonyms are components in the English language that are recognized as lexical items. Part of the challenge’s teachers face in trying to impart the knowledge of these lexical items is the fact that these items are not so easily taught or learned. In fact, many argue that these items are not at all teachable, and best acquired through vast reading. This paper will highlight the possibility of using a simple game called Speedy Lingo in helping students remember some homonyms, synonyms and antonyms. Speedy Lingo is a computer game that requires two players in which Player 1 is required to place the variable of the word/he/she wishes to ‘test’ Player 2 on. Player 2 will then provide the answers to the questions put forth by player 1. A total of 150 primary school students in Years 3 and 4 as well as 60 students in Form 4 (secondary school) in the states of Selangor and Perlis were given Pre-tests and Post-tests on the use of Synonyms, Homonyms and Antonyms and the results have indicated that instructions which are delivered via games not only help reduce teacher talk/instruction and increase self-directed learning but also aid greatly in quick memorization of synonyms, homonyms and antonyms of certain words.